VOLTAMMETRIC STUDY AND ANALYSIS OF CETIRIZINE DIHYDROCHLORIDE AND DEXTROCHLORPHENIRAMINE MALEATE ANTIHISTAMINES IN SURFACTANT MEDIUM BY USING CARBON PASTE ELECTRODE - Hattu, Nikmans
Development of analytical methods is focused on finding new methods that are practical, fast, economical, and having high sensitivity. Many analytical methods having high sensitivity for practical uses have been developed. In the field of electroanalysis, voltammetry method is the most widely used method to answer the challenge. This method has been proving to be able to analyze organic and inorganic analyte in trace concentration. By developing modified electrode with specific modifier combined with a compatible voltammetry technique, a more sensitive method can be obtained. Two voltammetry techniques that normally used to increase the sensitivity are square wave voltammetry and differential pulse voltammetry.